Geographic consistency in dominant, non-typeable Haemophilus influenzae genotypes colonising four distinct Australian paediatric groups: a cohort study. Issue 1 (December 2016) - Smith-Vaughan, Heidi; Beissbarth, Jemima; Bowman, Jacinta; Hare, Kim; Price, Erin; Pickering, Janessa; Lehmann, Deborah; Chang, Anne; Morris, Peter; Marsh, Robyn; Leach, Amanda
Abstract Non-typeableHaemophilus influenzae (NTHi)-associated ear and respiratory diseases (including pneumonia) represent a major health burden in many parts of the world. NTHi strains retrieved from the upper airways commonly reflect those found in the lower airways. Despite growing genomic and genotyping data on NTHi, there remains a limited understanding of global and regional NTHi population structures. The aim of this study was to determine whether nasopharyngeal carriage in four Australian paediatric groups at varying risk of NTHi colonisation was dominated by the same NTHi genotypes. Genotyping data generated by PCR-ribotyping were evaluated for 3070 NTHi isolates colonising the nasopharynges of Aboriginal and non-Aboriginal children enrolled in four longitudinal studies in three separate urban and remote regions of Australia. Several NTHi PCR-ribotypes dominated in nasopharyngeal carriage, irrespective of study setting. Principal coordinates analysis confirmed a cluster of common PCR-ribotypes among all cohorts. In conclusion, we identified dominant PCR-ribotypes common to geographically disparate Australian paediatric populations. Future genomic analyses will shed further light on the precise factors underlying the dominance of certain NTHi strains in nasopharyngeal carriage.